Improvement in water-holding capacity and structural stability of a sandy soil in northeast Thailand - Suzuki, Shinji; Noble, A.D.; Ruaysoongnern, Sawaeng; Chinabut, N. (2007)
Light textured sandy soils in northeast Thailand are often highly weathered and degraded resulting in low nutrient and water holding capacities. The latter is further complicated by the structural instability of these soils. Field based soil amelioration studies were undertaken in order to evaluate local traditional practices currently adopted by farmers and innovative approaches to improve the productivity of these soils. The treatments included: composted leaf litter, termite mound material, and bentonite. In the present study, physical properties associated with water holding capacity and soil structural stability of an upland soil of the Satuk series in Northeast Thailand were investigated two years after the application of these amendments. Although changes in silt and clay fraction were small, the application of these amendments enhanced porosity and altered the pore size distribution resulting in an increase in the available water content for crop growth. In particular, increases in the available water content were remarkably higher under termite mound material (0.21?m3 m-3) and bentonite (0.19?m3 m- 3) treatments when compared to the control (0.14?m3 m-3). However, soil structural stability remained poor for the compost and termite mound material treatments, while the structural stability was enhanced for the bentonite treatment. Enhanced soil structural stability observed in the bentonite treatment accounted for the persistence in increased water holding capacity, and this will have positive benefits to the rainfed cropping systems that are susceptible to periodic drought stress, thereby reducing risk of crop failure associated with low water holding capacity.